2006
DOI: 10.1084/jem.20061496
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 is a regulator of virus-specific CD8+ T cell survival in HIV infection

Abstract: Here, we report on the expression of programmed death (PD)-1 on human virus-specific CD8+ T cells and the effect of manipulating signaling through PD-1 on the survival, proliferation, and cytokine function of these cells. PD-1 expression was found to be low on naive CD8+ T cells and increased on memory CD8+ T cells according to antigen specificity. Memory CD8+ T cells specific for poorly controlled chronic persistent virus (HIV) more frequently expressed PD-1 than memory CD8+ T cells specific for well-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
798
5
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(876 citation statements)
references
References 48 publications
66
798
5
7
Order By: Relevance
“…Several groups have recently reported that PD-1 expression on peripheral blood CD8 þ T cells is increased during HIV infection and regulate T-cell survival. [34][35][36] Herein, we also demonstrated that induction of PD-1 is increased in Mes LNs of non-controllers and expression of PD-1 is enhanced in vitro by TGF-b. Although, we speculate a role of PD-1 in Mes LNs favoring immunosupression, a formal proof that blockade of PD-1/PD-L1 interaction will restore T-cell function and prevent death remains to be addressed once adequate reagents are available.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several groups have recently reported that PD-1 expression on peripheral blood CD8 þ T cells is increased during HIV infection and regulate T-cell survival. [34][35][36] Herein, we also demonstrated that induction of PD-1 is increased in Mes LNs of non-controllers and expression of PD-1 is enhanced in vitro by TGF-b. Although, we speculate a role of PD-1 in Mes LNs favoring immunosupression, a formal proof that blockade of PD-1/PD-L1 interaction will restore T-cell function and prevent death remains to be addressed once adequate reagents are available.…”
Section: Discussionsupporting
confidence: 55%
“…In HIV-infected individuals, it has been shown that blocking such interaction increases the capacity of peripheral blood HIV-specific CD8 þ T cells to proliferate and survive. [34][35][36] While TGF-b appears necessary to prime cells of SIV-infected macaques to undergo apoptosis, it is not sufficient in and by itself to fully induce the process, as we have been unable to induce death by simply adding TGF-b on T cells from healthy macaques, in spite of inducing PD-1 expression. This may however reflect the lack of PD-L1 expression in our in vitro culture system.…”
Section: Discussionmentioning
confidence: 83%
“…5 Increasing evidence demonstrates that upregulation of the PD-1 inhibitory receptor mediates HIV-specific CD8 1 T-cell functional exhaustion and CD8 1 T cell is apoptosis-sensitive, resulting in an impairment of CD8 1 T cell's ability to control virus replication. [6][7][8][9] Involvement of the PD-1 pathway has also been shown during hepatitis B and C virus infection [10][11][12][13] with PD-L1 expression demonstrated in situ on a wide variety of solid tumors including pancreas, lung, ovarian and bladder tumors. [14][15][16][17][18] Studies relating PD-L1 expression on tumors to disease outcome show that PD-L1 expression strongly correlates with unfavorable prognosis in kidney, bladder, gastric and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Cette observation est d'autant plus intéressante que cette enzyme, qui catabolisme le tryptophane et influence la capacité de prolifération des cellules, joue également un rôle sur la survie cellulaire [29]. De récents travaux ont décrit l'expression de la molécule PD-1 (programmed death molecule 1) par les lymphocytes T CD8 de patients infectés par le VIH-1 et de macaques infectés par le VIS [30][31][32][33][34]43]. Nos propres travaux indiquent une augmentation de l'expression de PD-1 dans les lymphocytes T CD8 isolés à partir des ganglions mésen-tériques.…”
Section: L'impact Du Métabolisme Cellulaire Dans L'apoptose Des Lymphunclassified